Effect of various mask types on athletic performance - Alexander, O.; Ciamacco, C.; Hershner, A. (ONU Student Research Colloquium, 2021)
Research surrounding the use of face masks during exercise has increased dramatically amid the COVID-19 pandemic. This IRB approved study aims to determine the effect of wearing either a cloth mask or a surgical mask while running on athletic performance. Athletic performance was measured, in seconds, by recording the time it took 18 subjects, ages 18-22, to each run 200 meters while wearing either of the two types of face masks. Heart rate, in beats per minute, was recorded before and after each of two running conditions. The time it took for the heart rate to return to the resting heart rate after each run was also recorded. The results were analyzed by means of a paired one-tail t-test. Data analysis revealed that there was not a significant effect of wearing either cotton or a surgical mask on athletic performance nor on heart rate recovery. Therefore, the difference in the breathing resistance of the surgical and cloth masks does not translate to a difference in athletic performance. Further research is needed to compare the effects of these masks to a no-mask control.